Profil Pencemaran Mikroplastik Pada Sedimen Ekosistem Mangrove di Pulau Serangan, Bali - Made Bayu Khrisna Pramana; Nyoman Dati Pertami; Ni Luh Gede Rai Ayu Saraswati (Program Magister Ilmu Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2025)
Microplastics are defined as small particles plastic with less than 5 mm in size. These small plastic particles were polluted all environments compartments, including mangrove ecosystem. This study aims to investigate microplastics pollution in mangrove sediment in Serangan waters, Bali. Moreover, sediment sample were collected in different sediment depth (0-10 cm, 10-20 cm and 20-30 cm) to understand the vertical abundance and morphology of microplastics in mangrove sediment. Sampling points were also distributed across mangrove ecosystem of Serangan Island with different characteristics, including near road and landfill station (St 1), residential area and small bussineses (St 2 and 3), and near bay area with less anthropogenic influence (St 4). A total of 182 suspected microplastic particles were identified from all sediment sample. The average of microplastics abundance vertically was ranging from 0.025±0.015 to 0.026±0.014 particle/g, while the average abundance horizontally was from 0.021±0.010 to 0.036±0.015 particle/g. Fragment was the most common microplastics types identified (76.37%), followed by fiber (15.38%) and film (8.24%). Our result highlight that microplastics has polluted the sediment layers of mangrove ecosystem in Serangan oWaters. The source of suspected microplastics particle in the sampling area was suggested from both land (through river pathway) and ocean (due to oceanographic factors, such as tides, wind and current). A further study on determining the polymer of suspected microplastics particle is needed. This is important to confirm the validity of visual identification in this study. Keyword: Microplastics, Mangrove ecosystem, Mangrove sediment, Serangan Island